Treatment of recurrent bronchial carcinoma: the role of high-dose-rate endoluminal brachytherapy - Hauswald, Henrik; Stoiber, Eva Maria; Rochet, Nathalie; Lindel, Katja; Grehn, Christian J.; Becker, Heinrich D.; Debus, Jürgen; Harms, Wolfgang (International journal of radiation oncology, biology, physics, 2010)
Purpose - This study's aim was to assess outcome and toxicity of high-dose-rate endoluminal brachytherapy (HDREB) for recurrent bronchial carcinoma. - Methods and Materials - From 1987 to 2005, 41 patients were treated with HDREB for symptomatic recurrent bronchial carcinoma. All patients had previously undergone external beam radiotherapy (EBRT) with a median dose of 56 Gy (range, 30-70 Gy). The median HDREB dose applied was 15 Gy (range, 5-29 Gy). The median time interval between primary EBRT and reirradiation was 9 months (range, 2-54 months). - Results - After a median follow-up of 6.7 months, the 6-, 12-, and 24-month overall survival rates were 58%, 18%, and 7%, respectively. The median overall survival time was 6.7 months. Local remission was achieved in 73% of patients (n = 30). A total of 24% of patients (n = 10) showed no response or progressive disease within 8 weeks after treatment. In 1 patient, treatment response was not documented. The 6-, 12-, and 24-month local control rates were 38%, 17%, and 3%, respectively. The median local progression-free survival time was 4 months (range, 1-23 months). Prognostic factors were a total dose of ≥15 Gy of HDREB (p = 0.029) and a Karnofsky performance score of ≥80% (p = 0.0012). The cause of death was locoregional progression in 27% of patients (n = 11), distant metastases in 24% of patients (n = 10), fatal hemorrhage in 15% of patients (n = 6), and other causes in 29% of patients (n = 12). None of the patients with locally controlled disease showed grade 3 or 4 late effects. - Conclusions - Palliative treatment of symptomatic, locally recurrent bronchial carcinoma with HDREB can effectively relieve symptoms in the majority of patients while causing only few complications. Still, time to progression is short.